Sistem Pendingin Otomatis Panel Surya Untuk Peningkatan Daya Output Berbasis Mikrokontroler - Rahajoeningroem, Tri; Jatnika, Ichsan (Telekontran : Jurnal Ilmiah Telekomunikasi, Kendali dan Elektronika Terapan, 2022)
Abstract - The solar panel will produce electrical energy according to the amount of light intensity it receives from the sun's rays,the temperature of the solar panel that works in the normal temperature standards (250C) will work optimally. If the temperature of the solar panel is too hot, it will decrease the performance of the solar cell. The purpose of this research is to design an automatic solar panel cooling system by flowing water on the back surface of the solar panel by making a plumbing pipe on the back of the solar panel made of aluminum. This test using a 50 Wp solar panel that uses cooling and without cooling. The average power yield of uncooled solar panels is 22.32 Watts and an efficiency of 12.62%, while the average power of solar panels using coolers is 27.8 Watts and the efficiency is 15.09%. When compared to uncooled solar panels, solar panels that use cooled efficiency are more than the efficiency increase of 2.47%.